2020
DOI: 10.1002/mnfr.202000381
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia Downregulate Brain Antioxidant Defense Enzymes and Neurotrophins in Rats: Assessment of the Modulatory Potential of EPA+DHA and Zerumbone

Abstract: Background: Oxidative stress (OS) plays a vital role in the pathogenesis of cognitive disorders. In this study, brain antioxidant defense dysregulation as a consequence of hyperlipidemia, and the efficacy of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA), and zerumbone (Z) in their modulation are assessed. Methods and results: Male Wistar rats are fed control, high-fat (HF), HF + fish oil (HF+F), HF + zerumbone (HF+Z), and HF + fish oil + zerumbone (HF+F+Z) diet for 60 days. Markers of OS, antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Besides the cardiovascular and metabolic disorders, hyperlipidemia has also been reported to affect brain functions ( Pappolla et al, 2003 ; Rahman et al, 2005 ; Thirumangalakudi et al, 2008 ; Cao et al, 2015 ; Ettcheto et al, 2015 ; Paul & Borah, 2017 ; Eriksson et al, 2017 ; Wang et al, 2018 ; Uppin et al, 2020 ; Dimache et al, 2021 ; Feringa & vander Kant, 2021 ). Cao et al (2015) reported that hyperlipidemia exacerbated cerebral injury of middle cerebral artery occlusion/reperfusion rats via oxidative stress, inflammation and neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the cardiovascular and metabolic disorders, hyperlipidemia has also been reported to affect brain functions ( Pappolla et al, 2003 ; Rahman et al, 2005 ; Thirumangalakudi et al, 2008 ; Cao et al, 2015 ; Ettcheto et al, 2015 ; Paul & Borah, 2017 ; Eriksson et al, 2017 ; Wang et al, 2018 ; Uppin et al, 2020 ; Dimache et al, 2021 ; Feringa & vander Kant, 2021 ). Cao et al (2015) reported that hyperlipidemia exacerbated cerebral injury of middle cerebral artery occlusion/reperfusion rats via oxidative stress, inflammation and neuronal apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The blood brain barrier (BBB) was observed to be compromised in hyperlipidemic animals and subsequently led to increased levels of total cholesterol (TC), total triglyceride (TG) and low-density lipoprotein (LDL)-cholesterol, and decreased high-density lipoprotein (HDL)-cholesterol in the brain ( Paul & Borah, 2017 ; Wang et al, 2018 ). There have been accumulating evidence that abnormal lipid metabolism may contribute to the pathogenesis of neurodegenerative diseases such as Alzheimer’s diseases (AD) and Parkinson’s diseases and the suggested mechanisms included impairment of BBB, amyloid deposition, pathological Tau accumulation, neuroinflammation and oxidative stress in the brain ( Pappolla et al, 2003 ; Rahman et al, 2005 ; Thirumangalakudi et al, 2008 ; Ettcheto et al, 2015 ; Paul & Borah, 2017 ; Eriksson et al, 2017 ; Uppin et al, 2020 ; Dimache et al, 2021 ; Feringa & vander Kant, 2021 ). However, not all of the research in the field found this association.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever a tissue injury occurs due to oxidate stress, the body releases antioxidant enzymes such as SOD, CAT, and GSH, which scavenge ROS in the liver [42]. Studies have shown that ZER prevents tissue injury by curbing the production of ROS [43][44][45]. The same mechanism is followed when paracetamol's cytotoxicity results in liver injury due to ROS generation [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that hyperlipidemia can reduce the activity of free radical scavengers, which would lead to a massive accumulation of lipid peroxides, thus accelerating the development of atherosclerosis. Meanwhile, the reduction of cerebral blood flow causes cerebral ischemia and hypoxia, and ultimately leads to brain damage and CI 16,17 . Moreover, it has been confirmed in recent studies that abnormally expressed LDL‐C, apolipoprotein A (Apo A), and apolipoprotein B (Apo B) have a close relationship with CI 18–20 .…”
Section: Overview Of Lipid Metabolism Disordersmentioning
confidence: 95%